2021
DOI: 10.3390/agronomy11050937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physiological and Quality Parameters of Green Asparagus Spears Subjected to Three Treatments against the Decline Syndrome

Abstract: Green asparagus (Asparagus officinalis L.) is a widely grown and consumed crop which provides high-level nutritional interest. In recent years, the decline syndrome in asparagus plantations has been rapidly augmenting. This syndrome causes the early death of whole plants, also negatively affecting the new replanting. Decline causes notable economic losses in the sector. The objective of this work was to verify the effect of different treatments against asparagus decline syndrome on the physiological parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The biofumigation of soil from site B had the most positive effect on asparagus root and shoot growth compared to steam-sterilisation or champost treatment. López-Moreno et al [26] also reported the positive effect of biofumigation with Brassica pellets on the yield of green asparagus in the first year of harvest.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The biofumigation of soil from site B had the most positive effect on asparagus root and shoot growth compared to steam-sterilisation or champost treatment. López-Moreno et al [26] also reported the positive effect of biofumigation with Brassica pellets on the yield of green asparagus in the first year of harvest.…”
Section: Discussionmentioning
confidence: 96%
“…The isothiocyanates produced during the degradation of the plant parts of the Brassicaceae family (mainly mustard flour) have antimicrobial, fungicidal, and nematocidal properties [25]. Lopez-Moreno et al [26] compared the effect of biofumigation with Brassica pellets, biofumigation with chicken manure pellets, and the disinfestation of the soil using Dazomet and concluded that the Brassica pellets and the chemical, Dazomet, were the most effective against the damage caused by the decline syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antioxidant capacity of plant tissues can be estimated by different tests, such as FRAP and TEAC. These assays are based on the capacity of different antioxidants to reduce pro-oxidants, using as oxidants some radicals like ABTS or ions such as Fe 2+ [35,65]. The application of HS to lettuce plants enhanced antioxidant capacity by both methods (root and foliar) at all doses (Figure 4A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Total GSH was assayed according to López-Moreno et al [35]. A total number of 0.1 g of plant material was macerated in 600 µL of 0.2 M HCl and then centrifugated at 16,000× g for 10 min.…”
Section: Antioxidant Quality Analysismentioning
confidence: 99%
“…The reasons for the phenomenon known as "asparagus decline" could be found in this practice. This phenomenon involves a decrease in crop yield over time and the inability to replant a particular piece of land for at least 5 years after the initial planting [18]. This limits the commercial lifetime of the plantation and leads to a continuous search for new lands for cultivation.…”
Section: Introductionmentioning
confidence: 99%